Rendering cross-conjugated azophenine derivatives emissive to probe the silent photophysical properties of emeraldine. Issue 32 (1st August 2017) - Lei, Hu; Langlois, Adam; Fortin, Daniel; Karsenti, Paul-Ludovic; Aly, Shawkat M.; Harvey, Pierre D.
Abstract : A fluorescent azophenine derivative was synthesized by coupling truxene and azophenine via the copper-free Sonagashira reaction using Pd2 (dba)3 and As(PPh)3 as catalysts. Abstract : An azophenine derivative was synthesized by coupling truxene and azophenine via the copper-free Sonagashira reaction using Pd2 (dba)3 and As(PPh)3 as catalysts. The crystal structure of this heavy azophenine model (∼4000) was made and the identity of the structure was confirmed. By introducing truxene groups into this cross-conjugated structure, the deactivating rotations around the NH–C6 H4 bonds were slowed down, which rendered this derivative near-IR emissive at 298 K. This species provided then the appropriate spectral and kinetic signatures for knowing where and what to look for in emeraldine, which was called non-emissive. Besides, two other compounds were also synthesized as models for this azophenine derivative for comparison and interpretation purposes.